The dynamics of HCV-specific antibody responses in HIV/HCV patients on long-term antiretroviral therapy - Lee, S.; Laiman, A.; French, M.; Flexman, J.; Watson, M.; Price, Patricia (Academic Press, 2017)
Antibody responses have not been fully characterised in chronically HIV/HCV patients receiving antiretroviral therapy (ART). Seventeen HIV/HCV patients receiving ART were followed for a median (range) interval of 597 (186–766) weeks. Prior to ART, HIV/HCV patients had lower levels of antibodies reactive with HCV core and JFH-1, and lower genotype cross-reactive neutralising antibodies (nAb) titres, than HCV patients. Levels of JFH-1 reactive antibody increased on ART, irrespective of CD4+ T-cell counts or changes in serum ALT levels. The appearance of nAb coincided with control of HCV viral replication in five HIV/HCV patients. In other patients, HCV viral loads remained elevated despite nAb responses. Sustained virological responses following HCV therapy were associated with reduced antibody responses to JFH-1 and core but elevated responses to non-structural proteins. We conclude that nAb responses alone may fail to clear HCV, but contribute to control of viral replication in some HIV/HCV patients responding to ART.